Organic semiconducting nanomaterials‐assisted phototheranostics in near‐infrared‐II biological window. Issue 1 (28th September 2020) - Yin, Chao; Lu, Xiaomei; Fan, Quli; Huang, Wei
Abstract: Phototheranostics conducted in the near‐infrared‐II (NIR‐II) biological window exhibits high superiorities relative to that conducted in the first near‐infrared (NIR‐I) window due to higher penetration depth, higher signal‐to‐noise ratio of imaging, and improved maximum permissible exposure. Currently, most existing agents developed for NIR‐II phototheranostics are limited to inorganic nanoparticles and small‐molecule dyes, which suffer from the issues of long‐term biotoxicity and poor photostability, respectively. Organic semiconducting nanomaterials (OSNs) constructed from π‐conjugated organic semiconducting polymers or oligomers have unique advantages including high photostability, flexible optical features, and good biocompatibility due to the totally organic and biologically inert constituents. These advantages make OSNs more promising for in vivo phototheranostics. We here make a brief review about recent progress of OSNs‐assisted phototheranostics conducted in the NIR‐II biological window. NIR‐II fluorescence imaging and photoacoustic imaging are mainly reviewed as diagnostic modalities to guide various treatments. Besides, multimodal phototheranostics using OSNs in NIR‐II window is also described. At last, the challenges and outlook for OSNs‐assisted NIR‐II phototheranostics are discussed. Abstract : Organic semiconducting nanomaterials (OSNs) prepared from π‐conjugated organic semiconducting polymers or oligomers have unique advantages for diverse biomedical applications, especially in vitro or in vivo bioimaging and imaging‐guided therapy. This contribution reviews the recent progress of OSNs‐assisted phototheranostics conducted in the NIR‐II biological window. With excellent biocompatibility and versatility, OSNs could be promising candidates for clinical translation in the future.